Causative constructions in Woirata, Kisar Island (Southwest Maluku, Indonesia) - Nazarudin, Nazarudin (UI Scholars Hub, 2015)
Woirata (or Oirata, see Van Engelenhoven in this volume) is closely related to Fataluku (Timor-Leste) and belongs to the Timor-Leste subgroup of the Timor-Alor-Pantar language family (TAP) together with Makalero and Makasai (Schapper, Huber, and Van Engelenhoven 2012). It has about 1,566 speakers. Taber (1993) suggests that there are 24 languages in Southwest Maluku of which 23 are Austronesian; Woirata is the only non-Austronesian language in the area. It is interesting to research in how far Woirata has been influenced by Austronesian languages. Because the Woirata and other people who live on Kisar Island, like the Meher, are using Melayu Tenggara Jauh (MTJ) as their lingua franca, one may expect deep language contact between Woirata and MTJ. This multilingual situation suggests a contact induced language change of Woirata, imposed by MTJ. This contribution aims to describe the causative constructions in Woirata and compare them with the counterpart constructions in MTJ and Meher.